2013
DOI: 10.1074/jbc.m113.470971
|View full text |Cite
|
Sign up to set email alerts
|

Nox4 NADPH Oxidase Mediates Peroxynitrite-dependent Uncoupling of Endothelial Nitric-oxide Synthase and Fibronectin Expression in Response to Angiotensin II

Abstract: Background: Oxidative stress is critical for the fibrotic response of mesangial cells (MCs) to angiotensin II. Results: Nox4-and mitochondrial reactive oxygen species (ROS)-dependent endothelial nitric-oxide synthase (eNOS) uncoupling led to fibronectin accumulation in MCs stimulated by angiotensin II. Conclusion: The Nox4/mitochondrial ROS/eNOS pathway mediates angiotensin II-induced MC injury. Significance: Targeting Nox4 and mitochondrial ROS is a promising therapeutic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(117 citation statements)
references
References 78 publications
5
108
1
3
Order By: Relevance
“…Mitochondrial oxidative stress is a key mechanism in the onset and propagation of cardiovascular diseases as loss of MnSOD results in dilated cardiomyopathy and limits the survival of mice to 2 weeks (5). Increased mitochondrial oxidative stress also occurs due to an activated renin-angiotensin system that impacts heart and the vascular system, and it has also been implicated in hypertension (41,42). This study shows a redox regulatory mechanism in MKK4 activation resulting in MnSOD activation in ECs.…”
Section: Discussionmentioning
confidence: 64%
“…Mitochondrial oxidative stress is a key mechanism in the onset and propagation of cardiovascular diseases as loss of MnSOD results in dilated cardiomyopathy and limits the survival of mice to 2 weeks (5). Increased mitochondrial oxidative stress also occurs due to an activated renin-angiotensin system that impacts heart and the vascular system, and it has also been implicated in hypertension (41,42). This study shows a redox regulatory mechanism in MKK4 activation resulting in MnSOD activation in ECs.…”
Section: Discussionmentioning
confidence: 64%
“…First, increased generation of metabolic intermediates may be toxic. Succinate, a ligand of the G protein-coupled receptor GPR91, can activate the renin-angiotensin system (39)(40)(41), and the activation of angiotensin II may result in NADPH oxidase 4-generated (Nox4-generated) mitochondrial oxidative damage (42,43), leading to a feed-forward mechanism that promotes kidney injury in diabetes. Fumarate, which also accumulates in the diabetic kidney and urine of a type 1 model of DKD, is a potent inducer of HIF-1α and TGF-β, both of which could contribute to kidney disease pathology (44).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Ang II can induce eNOS uncoupling and thereby reduce NO bioavailability and increase oxidative stress. 67,68 Moreover, we recently found that renal Ang II content is augmented, and renal CAT1 expression is reduced in diet-induced obese hypertensive mice. 5 To determine whether augmented Ang II levels can reduce renal l-arginine transport, we examined the effects of exogenous Ang II on 3 H-l-arginine transport in renal and endothelial cells.…”
Section: Mechanistic Insights Activation Of the Raas As A Mediator Ofmentioning
confidence: 99%
“…Por ejemplo, la Ang II puede inducir el desacople de la eNOS y, por lo tanto, disminuir la biodisponibilidad de NO y aumentar el estrés oxidativo. 67,68 Además, recientemente hallamos que en ratones hipertensos obesos con dieta inducida el contenido de la Ang II en el riñón aumenta y la expresión del CAT1 renal se reduce.…”
Section: Perspectivas Mecanicistasunclassified